Efeito da maturação seca e úmida na qualidade da carne de matrizes suínas de descarte - Teixeira, Everton de Oliveira (2022)
The disposal of sows is a common practice in commercial farms around the world, however the meat of animals of this productive category is commonly associated with quality problems, in this way, the objective of this study was to evaluate the use of two maturation methods (dry and wet) and their impacts on the physical-chemical attributes and quality of meat from culling sows. For this purpose, 25 samples of loin (Longíssimos dorsi) were used from five discard matrices with ± 5.5 years of age and average weight of 247 ± 25 kg. The treatments consisted of dry maturation (DM), wet maturation (WM) and control (fresh meat). The treatments with maturation were submitted to two storage times (7 and 14 days). Samples measuring approximately 13 ± 2 cm and 700 ± 170 g were collected from each loin at 0, 7 and 14 days, submitted to the maturation processes to carry out the physicochemical analyses. An increase in pH was observed with the maturation processes (p <.0001). Liquid losses during ripening (PLM), thawing (PLD) and cooking (PLC) were directly affected by the ripening processes (p <.0001). PLD showed an inversely proportional behavior to PLM. As for the chemical composition of the meat, in the WM process, the mineral matter content was affected (p <0.025), however, the DM affected the moisture, crude protein and mineral matter values (p <.0001). There was an increase in lipid oxidation (TBARs) in MS (p = 0.001), as well as in softness, shear force - WBSF (p = 0.0002) and myofibril fragmentation index - MFI (p = 0.021), when compared in natura meat with the other treatments, the color parameters (L*, a* and b*) did not change. Therefore, it was concluded that the nutritional and physicochemical characteristics of the meat from the culling swine matrices were affected with the maturation, being the DM and the time of 14 days that most affected the quality of the meat studied.